Biomedical omics: first insights of a new MSc degree of the University of Milan. Issue 1 (February 2022) - Alcalay, Myriam; Jereczek-Fossa, Barbara Alicja; Pepa, Matteo; Volpe, Stefania; Zaffaroni, Mattia; Fiore, Francesca; Marvaso, Giulia; Pravettoni, Gabriella; Curigliano, Giuseppe; Santaguida, Stefano; Pelicci, Pier Giuseppe
The advent of technologies allowing the global analysis of biological phenomena, referred to as "omics" (genomics, epigenomics, proteomics, metabolomics, microbiomics, radiomics, and radiogenomics), has revolutionized the study of human diseases and traced the path for quantitative personalized medicine. The newly inaugurated Master of Science Program in Biomedical Omics of the University of Milan, Italy, aims at addressing the unmet need to create professionals with a broad understanding of omics disciplines. The course is structured over 2 years and admits students with a bachelor's degree in biotechnology, biology, chemistry, or pharmaceutical sciences. All teaching activities are fully held in English. A total of nine students enrolled in the first academic year and attended the courses of radiomics, genomics and epigenomics, proteomics, and high-throughput screenings, and their feedback was evaluated by means of an online questionnaire. Faculty with different backgrounds were recruited according to the subject. Due to restrictions imposed by the coronavirus disease 2019 (COVID-19) pandemic, laboratory activities were temporarily suspended, while lectures, journal clubs, and examinations were mainly held online. After the end of the first semester, despite the difficulties brought on by the COVID-19 pandemic, the course overall met the expectations of the students, specifically regarding teaching effectiveness, interpersonal interactions with the lecturers, and courses organization. Future efforts will be undertaken to better calibrate the overall workload of the course and to implement the most relevant suggestions from the students together with omics science evolution in order to guarantee state-of-the-art omics teaching and to prepare future omics specialists.